Dual Case Reports for Lipid Loss from Human Hair - Song, Sang-Hun; Son, Seong Kil; Kang, Nae-Gyu (Archives of Clinical and Medical Case Reports, 2019)
This study aims to understand the mechanism of lipid loss from the hair upon contact with surfactants. We herein proposes that the process of lipid loss can be categorized into two mechanisms. In the first mechanism, the lipids inside the hair diffuse through the cell membrane complex (CMC) to the outermost layer of hair and are removed by a roll-up mechanism. In the second mechanism, the surfactant that penetrates hair directly emulsifies the lipids. The mechanism of lipid loss depends on the relative <gwmw class="ginger-module-highlighter-mistake-type-1" id="gwmw-15755303530041321372161">hydrophobicity</gwmw> of the lipid. Highly hydrophobic lipids, such as <gwmw class="ginger-module-highlighter-mistake-type-1" id="gwmw-15755303549999320980699">squalene</gwmw> and wax esters, are primarily lost through the penetration pathway, while relatively less hydrophobic lipids, such as fatty acids and cholesterol, follow the roll-up mechanism. These mechanisms were validated by confirming that surface and internal modifications of hair protected different types of lipids from the surfactant treatment.